Ungdomars väg från skola till arbetsliv - nordiska erfarenheter - Panican, Alexandru; Olofsson, Jonas (Nordiska ministerrådet, 2008)
This report highlights the conditions for young people trying to establish themselves in the labour market in the Nordic countries. The aim has been to examine similarities and differences with regard to specific aspects of the welfare systems with a focus on upper secondary school level and political initiatives in the labour market. The passage of students through upper secondary school, transition, has been at the forefront in the study of the countries. In several chapters, the authors have referred to international youth research and working life research. The aims of welfare policy in the Nordic countries are similar. However, the report shows that conditions for young people to be able to support themselves and establish themselves in the labour market are different. The Nordic countries have different systems to regulate the transition of young people from school to working life. There are large variations in both the design of vocational education at upper secondary school level and political initiatives in the labour market. The report shows that the design of the systems has an impact on the conditions for young people to establish themselves in the labour market. Some of the large variations that can be seen in transition, employment rates and relative rates of employment among young people and young adults in the Nordic countries can be reasonably explained by differences in the design of vocational education at upper secondary school level and labour market policy. Labour market conditions for young people are less favourable in Finland and Sweden than in the other Nordic countries, although the situation in Finland has improved significantly in recent years. Conditions for young people are most favourable in Iceland, if only the unemployment rates and proportion of employed are taken into account. However, in Iceland there are still a relatively high proportion of young adults who have not completed upper secondary education and this can create problems in the future. Similarities in vocational ...